2020
DOI: 10.3390/cancers12092604
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Classification of Endometrial Stromal Sarcomas Using RNA Sequencing Defines Nosological and Prognostic Subgroups with Different Natural History

Abstract: A series of 42 patient tumors diagnosed as endometrial stromal sarcoma (ESS) based on the morphology but negative for JAZF1 and/or YWHAE rearrangement in FISH was analyzed by RNA-sequencing. A chromosomal rearrangement was identified in 31 (74%) of the cases and a missense mutation in known oncogenes/tumor suppressor genes in 11 (26%). Cluster analyses on the expression profiles from this series together with a control cohort composed of five samples of low grade ESS harboring a JAZF1-SUZ12 fusion, one high gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…A recent study also showed that small round cell sarcomas with distinct fusions (e.g., CIC-fused and BCOR-rearranged tumours) had unique transcriptomic profiles 25 . Further reinforcing the idea that transcriptomics has a role in the molecular classification of fusion driven sarcomas, the same group showed that consensus clustering of gene expression data in endometrial stromal sarcomas (ESS) was capable of identifying a high grade group comprised of tumours harbouring BCOR rearrangements, and a low grade group composed of tumours with a fusion of a PRC2 zinc finger protein (such as JAZF1 and PHF1) 26 . Interestingly, YWHAE-NUTM2 positive ESS which is typically considered a clinically aggressive subtype was found to be split in the high grade and low grade clusters, indicative of molecular heterogeneity within this fusion positive ESS 26 .…”
Section: Introductionmentioning
confidence: 84%
“…A recent study also showed that small round cell sarcomas with distinct fusions (e.g., CIC-fused and BCOR-rearranged tumours) had unique transcriptomic profiles 25 . Further reinforcing the idea that transcriptomics has a role in the molecular classification of fusion driven sarcomas, the same group showed that consensus clustering of gene expression data in endometrial stromal sarcomas (ESS) was capable of identifying a high grade group comprised of tumours harbouring BCOR rearrangements, and a low grade group composed of tumours with a fusion of a PRC2 zinc finger protein (such as JAZF1 and PHF1) 26 . Interestingly, YWHAE-NUTM2 positive ESS which is typically considered a clinically aggressive subtype was found to be split in the high grade and low grade clusters, indicative of molecular heterogeneity within this fusion positive ESS 26 .…”
Section: Introductionmentioning
confidence: 84%
“…Novel fusions that have been recently detected using RNA sequencing include KAT6B-KANSL1, RNF111-ARID2, ESR1-NCOA3, PTCH1-GLI1, SYNGAP1-JAZF1, PHF21A-NFIA, PHF21A-CETP, ACTB-GLI1 and GREB1-NCOA2 [ 89 ].…”
Section: Endometrial Stromal Nodule (Esn) and Low-grade Endometriamentioning
confidence: 99%
“…Some LG-ESSs harbouring YWHAE-NUTM2 fusion, which is a molecular characteristic of high-grade endometrial sarcomas, have also been reported [ 89 , 90 ].…”
Section: Endometrial Stromal Nodule (Esn) and Low-grade Endometriamentioning
confidence: 99%
See 2 more Smart Citations